Pelaksanaan dan Sistem bagi Hasil Pembiayaan Al-Mudharabah pada Bank Muamalat di Rangkasbitung - Diny Mutiara; Muhamad Rizal; Qaila Sofiani; Megania Kharisma (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
This study aims to comprehensively examine the implementation and mechanisms for results in Al-Mudharabah financing at Bank Muamalat Rangkasbitung, while also assessing the level of compliance of its implementation with sharia principles. This study applies a qualitative descriptive method with a field study approach involving direct observation, interviews, and review of documents related to Mudharabah financing procedures. The research findings show that Bank Muamalat Rangkasbitung implements a profit-sharing system based on the principles of justice (al-'adl) and trustworthiness (al-amanah). The profit-sharing scheme is carried out proportionally according to the ratio agreed upon in the initial contract, so that both parties have clarity regarding rights and responsibilities. The implementation of this system not only ensures the avoidance of usury but also strengthens the partnership between the bank and customers through practices of transparency, information disclosure, and a shared commitment to business management. Overall, these findings show that the implementation of Al-Mudharabah financing at Bank Muamalat Rangkasbitung has been running in line with several sharia values ​​and even supports the realization of fair, ethical, and sustainability-oriented Islamic economic practices. Thus, Mudharabah financing at the branch can be an example of the effective implementation of sharia contracts and is able to encourage the development of the sharia financial sector at the local level.